The Role of the Internal Control System on the Management Performance of Batara Guru Hospital Belopa City, Luwu Regency - Rahmi, Rahmi; Usman, Halim; Pratiwi, Indah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aims to determine the role of the internal control system on the management performance of Batara Guru Hospital. The method used is quantitative research with data collection through questionnaires. The population is 127 employees, and the sampling technique used is full sampling, but only 70 respondents provided complete data. Data analysis was carried out using simple linear regression using SPSS version 21. The results of the study indicate that the internal control system has a significant effect on management performance. This finding emphasizes the importance of strengthening internal control as a strategic tool in supporting the achievement of organizational goals and improving service quality. The novelty of this study lies in its focus on regional health service institutions that are rarely studied with a quantitative approach based on empirical data. Its originality is strengthenend by the use of empirical data directly from employees and a relevant quantitative approach. Conclusion an effective internal control system is essential for management performance. Hospitals are advised to continue to strengthen this system for better service.